THE LEVEL OF ETHICAL LEADERSHIP ACCORDING TO THE PRINCIPLE OF RESPECT AMONG SCOUT LEADERS IN SCHOOLS AND CAMPS - Asst. Lect Ammar Jabbar Ghali; Prof. Dr. Riad Nouri Abbas (Scholars Digest Publishing, 2024)
Ethical leadership is considered one of the forms of leadership through which an individual can be given the moral virtues that make him a good person useful to his society and his country. It is one of the topics that various educational institutions have paid attention to, based on the necessity of adhering to moral values and the ability to manage educational institutions with ethical behaviors. Moral leadership is It begins with the leader’s practice of the moral values of respect, justice, integrity, objectivity, honesty, and honesty in performing administrative and educational duties. The study aimed to build a measure of ethical leadership according to the principle of respect for scout leaders, and to identify their level of ethical leadership. The researchers used the descriptive approach, and the research sample represented scout leaders in schools and camps. The Scout Leader is one of the focuses of the activities that take place in Scout schools and camps, because he is responsible for attracting individuals, training them, and guiding them. Therefore, those in charge of this movement paid great attention to the process of selecting leaders. An individual can be successful within educational institutions and in the field of the Scout Movement if he possesses it. Some good qualities.
Keywords: Ethical leadership: Respect: Scout Leader.